Layanan Kajian Pra Riset Berbasis Literature Review dan Bibliometrik Di Pusat Data dan Dokumentasi Ilmiah LIPI - Tupan . (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2021)
(Objectives) A literature review and biliometric based pre-research service review was conducted at the Center for Scientific Data and Documentation of the Indonesian Institute of Sciences.(Method) Reviews of literature review and bibliometric services were carried out by tracing methods from various sources of information both from within and outside the country, namely for domestic information sources used were ISJD.pddi.lipi.go.id, https://garuda.ristekbrin.go.id/, and https://moraref.kemenag.go.id/. Meanwhile, foreign databases consist of Scopus and Web of Science. The search results of manuscripts that are in accordance with bibliometric-based pre-research services and literature reviews are analyzed descriptively as a result and discussion. (Findings) The results of the study show that literature review services can help analyze certain topics as a consideration in conducting research. Literature reviews can also encourage objective thinking, and a systematic approach to the research to be carried out. Meanwhile, the bibliometric service helps researchers evaluate research results by looking at the bibliometric map. With the bibliometric visualization map, it can be seen that research topics are rarely conducted which are the basis for researchers to conduct further research.